Ensuring a Turning Point with Political Ideology and Cultural Knowledge to Achieve the 2045 Vision - Abadi, Mansurni; Widjaja, Nicho Hadi; Ishak, Shahrial Bin; Olausson, Peter (Badan Pembinaan Ideologi Pancasila, 2022)
The literature analyzing perspectives on Indonesia's golden years in the 2045 narrative is extensive and optimistic. But achieving 2045 is more challenging amid disruption conditions, especially after a multidimensional crisis because of COVID-19. Cite Sukarno's term about the years of Vivere Pericoloso, an Italian phrase that means life is full of danger, making our future toward 2045 uncertain. But the years of Vivere Pericoloso are also the right moment to perfectly achieve the ideals, principles, goals, efforts, and logic of the Indonesia 2045 vision. Culture and politics are two important components that can make our turning point toward 2045 come true. Our findings are political ideology based on expansive penetration with internalization and consistency using indoctrination method toward